Effect of colony stimulating factor on murine macrophages. Induction of antitumor activity. - Wing, E J (1982)
Colony stimulating factor (CSF) was assessed for its capacity to stimulate antitumor activity in macrophages. Murine peritoneal macrophages incubated with CSF for 48 h inhibited [3H[thymidine (TdR) incorporation by P815 tumor cells to approximately 20% of control values. Inhibition of CSF-stimulated macrophages was significantly greater than inhibition by unstimulated macrophages (P less than 0.001). CSF had little direct effect on the proliferation of either tumor cells or macrophages alone, indicating that the antitumor activity of CSF was mediated by macrophages. it is unlikely that impurities in the CSF preparations were responsible for the effect since CSF that had been purified to homogeneity was as active as crude preparations. Furthermore the activity of CSF on macrophages was blocked by addition of purified anti-CSF antibodies. In addition to being tumoristatic, CSF-stimulated macrophages were tumoricidal as determined by a tumor colony growth assay. Tumor cells that had been incubated with CSF-stimulated macrophages showed a significant reduction in tumor colony-forming units (P less than 0.01). Thus, in addition to its effect on hemopoietic stem cells, CSF induces certain effector functions in mature macrophages that may enhance endogenous antitumor host defenses.